2008
DOI: 10.1111/j.1540-4781.2008.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Focus on Form in University Spanish Literature Courses

Abstract: Incidental focus on form is one of several ways to direct language learners' attention to formal aspects of language within meaningful communicative contexts. Learners can benefit from focus on form, but the extent to which incidental focus on form, or any other type, is available to learners in advanced foreign language literature classes has not been widely researched. In a multiple case study approach, three university Spanish literature classes were studied over the course of a 15-week semester. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 52 publications
5
61
0
1
Order By: Relevance
“…In a multiple case study of three university Spanish literature classes, Zyzik and Polio (2008) found that teachers preferred to use recasts for correcting errors because it did not embarrass the learners. The authors speculated that the short utterances produced by the learners might have been the reason the teachers used this type of feedback predominantly and that other types of feedback involving negotiation might have been considered more time-consuming.…”
Section: Effectiveness Of Promptsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a multiple case study of three university Spanish literature classes, Zyzik and Polio (2008) found that teachers preferred to use recasts for correcting errors because it did not embarrass the learners. The authors speculated that the short utterances produced by the learners might have been the reason the teachers used this type of feedback predominantly and that other types of feedback involving negotiation might have been considered more time-consuming.…”
Section: Effectiveness Of Promptsmentioning
confidence: 97%
“…Several studies (Mackey et al 2004;Mori 2011;Polio et al 2006;Zyzik and Polio 2008) have examined how individual teachers' views about their lessons, their learners, learning and teaching atmosphere may affect their use of incidental focus on form techniques. However, these studies have a number of limitations that we will try to address in the present study.…”
Section: The Research Gapmentioning
confidence: 99%
“…These pedagogical moves -accepting Ana's assurance and anticipating future difficulties as matters of spelling rather than meaning -preclude Ana from having to demonstrate her comprehension. Some of this lack of "negotiation of meaning" may be due to a preference for indirect correction (Zyzik & Polio, 2008), a concern for helping Ana "save face" (Musumeci, 1996) by not forcing her to prove her knowledge, or the teacher's assumption that Ana would in fact signal her lack of comprehension if she did not understand the language being used.…”
Section: Transcript 3bmentioning
confidence: 96%
“…Scholars have argued that the language-content or languageliterature 'gap' that exists between courses in the basic-intermediate and upper-level course sequences often makes third-year language learning problematic (Brandes & Rettig, 1986;Brown, Bown, & Egget, 2009;Kraemer, 2008;Lord, 2014;Paesani, 2011). Students who are used to learning the grammatical and lexical patterns in beginning and intermediate courses need help learning to function in upper-level courses, which tend to focus primarily on content, typically literature (Zyzik & Polio, 2008). Examining third-year foreign language (FL) courses thus presents an opportunity to discover the ways that languagelearning tasks can be effectively integrated across these sequences.…”
Section: Introductionmentioning
confidence: 98%